Association of regional disparity of obstetrics and gynecologic services with children and infants mortality rates: A cross-sectional study - Sogand Tourani; Mohammad Zarezadeh; Mehdi Raadabadi; Fatemeh Pourshariati (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Equity in distribution of resources is considered as an important priority in health care systems. Equitable distribution of obstetrics and gynecology (Ob/Gyn) services in the country level is critical in maternal and neonatal health for qualitative promotion of maternal care in pregnancy, delivery, and post-delivery periods. Objective: The present study aimed at determining regional disparity of obstetrics and gynecology services and its association with children and infants mortality rates. Materials and Methods: This was a descriptive-analytical study conducted in 2015 to investigate distribution of Ob/Gyn services using three indicators of number of nursing and midwifery personnel, total Ob/Gyn specialists, and total delivery beds among 30 provinces of the country. Equity criteria in the present study included population, normal vaginal deliveries, cesarean sections, and total deliveries. Data were gathered using a researcher-made form and Stata 12 was used to calculate Gini coefficient. The association of Ob/Gyn services with children and infant mortality rates was investigated using SPSS package and linear regression test. Results: The lowest Gini coefficient was observed in distribution of nursing and midwifery personnel in delivery wards in terms of vaginal delivery (0.38 from 1) and the highest value was related to distribution of Ob/Gyn specialists in terms of vaginal delivery (0.73 from 1). Infant mortality was significantly associated with number of nursing and midwifery personnel in delivery wards, and total number of Ob/Gyn specialists. Conclusion: Considering new population policies in Iran and increased fertility rate, it is recommended to facilitate accessibility of the required services for the women, particularly those of reproductive age.